A non-conditioned bone marrow transplantation mouse model to study clonal hematopoiesis and myeloid malignancies - Sofia Bentivegna; Marwa Almosailleakh; Lin-Pierre Zhao; Mikkel Bruhn Schuster; Sébastien Benquet; Alexander Balhuizen; Helga Fibiger Munch-Petersen; Lene Dissing Sjö; Mads Hald Andersen; Nicolas Dulphy; Bo Porse; Kirsten Grønbæk (Experimental Hematology & Oncology)
Abstract Clonal hematopoiesis of indeterminate potential (CHIP) is a condition where blood or bone marrow cells carry mutations associated with hematological malignancies. Individuals with CHIP have an increased risk of developing hematological malignancies, atherosclerotic cardiovascular disease, and all-cause mortality. Bone marrow transplantation (BMT) of cells carrying CHIP mutations into irradiated mice are useful procedures to investigate the dynamics of clonal expansion and potential therapeutic strategies, but myeloablative conditioning can induce confounding effects. We established a non-conditioned BMT model using C57BL/6J-Kit W-41J /J (W41) recipient mice to overcome the unwanted effects of irradiation. Conditional Tet2 deletion using tamoxifen was used to obtain Tet2 −/− cells from donor mice. Total BM Tet2 −/− cells were transplanted into W41 recipients, and longitudinal and terminal analyses at 10 months post-BMT were performed. We showed that W41 mice can be used for BMT procedures without myeloablative pre-conditioning. The transplantation of Tet2 −/− BM cells led to a progressive expansion of the donor cells in W41 recipients. By modulating the numbers of Tet2 −/− cells transplanted, recipient mice developed features of clonal hematopoiesis or myeloid malignancies. In conclusion, our model is an alternative to conventional irradiation-based transplantation models to study mechanisms underlying malignant hematopoiesis without confounding effects derived from pre-conditioning regimen.